Active Cooling Camera Modification for Improved Astronomy Data Collection - Christopherson, Christopher (Proceedings of the Wisconsin Space Conference, 2017)
Using Digital Single Lens Reflex (DLSR) cameras modified to be sensitive into the infrared are an inexpensive entry into astrophotography. Such a camera was used for wide-field, narrowband observations of the Cygnus Superbubble in the Observing Nebulosities project (Christopherson and Kaltcheva, 2015). One of the downfalls to using a DLSR for such a study is the inefficiency of collecting data from the buildup of heat in the sensor during data collection and the noise introduced into the images as a result. For this project an active cooling modification was designed and installed on a DSLR camera allowing the camera sensor to be cooled and held at a temperature below ambient conditions to reduce noise in speed up the data collection process.